A Systematic Review of The Implementation of Projek Penguatan Profil Pelajar Pancasila (P5) in Indonesian Schools (2020–2024) - Firoh, Luluk Magh; Raharjo , Tri Joko; Sukasih, Sri; Subali, Bambang; Widiarti, Nuni (FKIP - Universitas Riau, 2025)
The implementation of the Pancasila Student Profile Strengthening Project (P5) is one of the key pillars of the Merdeka Curriculum, aiming to shape students with holistic character and global competitiveness. However, its application across educational institutions presents varying dynamics, depending on school readiness, available resources, and understanding of the targeted character dimensions. This study aims to systematically examine the implementation practices of P5 in primary and secondary schools during the period of 2020–2024. The method employed is a Systematic Literature Review based on PRISMA guidelines, involving the analysis of 25 academic articles sourced from national and international databases. The findings indicate that P5 generally contributes to the strengthening of character values such as collaboration, independence, and love for the nation. The most commonly used implementation strategy is the Project-Based Learning approach, often integrated with local cultural themes. Nonetheless, several key challenges remain, including the lack of teacher training, limited school infrastructure, and uneven understanding of the P5 framework. This review highlights the importance of structural support and the continuous development of educator capacity to ensure that P5 can be implemented effectively and equitably across educational settings in Indonesia.